Unravelling potential biomarkers for acute and chronic brucellosis through proteomic and bioinformatic approaches - Yang, Yuejie; Qiao, Kunyan; Yu, Youren; Zong, Yanmei; Liu, Chang; Li, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
This study aimed to identify potential biomarkers associated with acute and chronic brucellosis by employing advanced proteomic and bioinformatic methodologies. Blood samples from 24 individuals with acute brucellosis, 24 individuals with chronic brucellosis, and 12 healthy controls were analyzed. 763 differentially expressed proteins (DEPs) were identified using differential expression analysis, and two co-expression modules associated with brucellosis clinical traits significantly were identified with weighted gene co-expression network analysis (WGCNA). A total of 25 DEPs were identified in all three pairwise comparisons, and 20 hub proteins of one significant module were identified in the WGCNA analysis. Nine proteins overlapped between the 25 DEPs and 20 hub proteins, highlighting their potential importance in brucellosis. A random forest model based on these nine proteins demonstrated good classification performance for the three groups. Enrichment analysis revealed that these proteins are involved in various biological processes, including inflammation, coagulation, extracellular matrix regulation, and immune response. Our results offer valuable insights into potential therapeutic targets or diagnostic biomarkers for brucellosis.